2013
DOI: 10.1089/sur.2012.195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Diabetes Mellitus on Clinical Outcomes in Patients with Peritoneal Dialysis-Related Peritonitis

Abstract: Old age and diabetes mellitus are two major risk factors for adverse outcomes of PD-related peritonitis. Although they are not contraindications to PD, our results suggest that these patients need meticulous care when peritonitis occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Piccoli et al (37) previously reported that the direct mortality of PD-related peritonitis increased with age. Similarly, Lim et al (38) showed that older patients have a higher peritonitis-related mortality than young patients, and Tsai et al (39) found that old age and diabetes are the 2 major risk factors for adverse outcomes of PD-related peritonitis. Specifically, Barretti et al (40) noted that the outcome of PD-related peritonitis due to Staphylococcus aureus is negatively influenced by age and diabetic status.…”
Section: Treatment Of Pd-related Infectionsmentioning
confidence: 96%
“…Piccoli et al (37) previously reported that the direct mortality of PD-related peritonitis increased with age. Similarly, Lim et al (38) showed that older patients have a higher peritonitis-related mortality than young patients, and Tsai et al (39) found that old age and diabetes are the 2 major risk factors for adverse outcomes of PD-related peritonitis. Specifically, Barretti et al (40) noted that the outcome of PD-related peritonitis due to Staphylococcus aureus is negatively influenced by age and diabetic status.…”
Section: Treatment Of Pd-related Infectionsmentioning
confidence: 96%
“…It seems highly probable that touch contamination and bowel dysfunction are important underlying causes of peritonitis episodes in older PD patients [22]. Diabetic mellitus and low education were risk factors of PD-related peritonitis in previous studies [22][23][24]. As diabetes mellitus is regarded as a risk factor for infections in general, it seems to be reasonable to consider it also as a risk factor for peritonitis in PD patients [24].…”
Section: Prevalence Peritonitismentioning
confidence: 95%
“…More recently, retrospective studies found that older age (more than 65 years) was the only identi ed risk factor associated with peritonitis [20,21]. It seems highly probable that touch contamination and bowel dysfunction are important underlying causes of peritonitis episodes in older PD patients [22]. Diabetic mellitus and low education were risk factors of PD-related peritonitis in previous studies [22][23][24].…”
Section: Prevalence Peritonitismentioning
confidence: 99%
“…These encouraging trends suggest that modality selection is becoming more appropriate as the selection of older patients with comorbidity is at variance with benefits suggested by registry analyses and observational studies . Both peritonitis and death from peritonitis have been associated with advanced age at the start of PD and with diabetes mellitus …”
Section: Improving Patient Outcomesmentioning
confidence: 99%
“…42,43 Both peritonitis and death from peritonitis have been associated with advanced age at the start of PD and with diabetes mellitus. 44,45 Select motivated patients and consider the need for support Success with PD requires significant patient motivation and self-support. 1 This may be supplemented with support from friends, partners and other family members.…”
Section: Consider Peritoneal Dialysis For Patients <60 Years Without mentioning
confidence: 99%